Knowledge and practices of NFPE-AG graduates regarding menstruation - Ali, Ahmed; Mahmud, Shah Noor; Karim, Fazlul; Chowdhury, AMR (BRAC Research and Evaluation Division (RED), 2019)
BRAC canied out a two-year Non-Fonnal Primary Education Programme for Adolescent Girls (NFPE-AG) as part of its fanner Women's Heath and Development Programme (WHOP) to increase basic literacy and nwneracy skills as well as awareness on reproductive health, nutrition and social issues. The first phase of .NFPE-AG was started in September 1991 through 1000 schools in 10 thanas of WHDP and ended in August 1993. This study was undertaken to assess the level of knowledge retained vis-a-vis practices ofNFPE-AG graduates regarding menstruation. A total of 30 fonner NFPE-AG schools (closed 2 years back) were selected from 6 WIIDP areas (5 schools from each area). From each schooL 7 NFPE-AG graduates aged 15-19 years who did not continue their study in fonnal schools after graduation were selected. Seven other girls aged 15-19 years with no schooling (NS-AG) were selected from the adjacent villages of each fanner NFPE-AG school as comparison group. Thus, a total of 420 adolescent girls (210 from each group) were interviewed in January 1996.